Decree No. 2 of the Year 2017 Amending Certain Provisions of Law No. 21 of the year 1958 Concerning the Organization and Promotion of Industry = قانون رقم 2 لسنة 2017 بتعديل بعض أحكام القانون رقم 21 لسنة 1958 فى شأن تنظيم الصناعة وتشجيعها - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic